THE RELATIONSHIP OF MICRONUTRIENTS AND ORAL MUCOSA DISEASES: A SYSTEMATIC REVIEW - Desi Elvhira Rosa; Nanan Nur’aeny (FKG Unlam, 2022)
Background: The association between micronutrients and oral mucosa diseases have been studied for a long time by many researchers. Nutritional deficiency can significantly interfere the function of the oral cavity. Various diseases in the oral cavity can occur due to nutritional deficiencies, especially micronutrient deficiencies. Purpose: This study aimed to systematically evaluate recently studies that investigating micronutrient level in patients with oral mucosa diseases to determine the relationship of micronutrients and oral mucosa diseases. Method: Electronic databases were searched from January 2011 to June 2021 for studies that measured the micronutrients level in patients with oral mucosa diseases. Only case-control studies in human reporting serum, salivary and urine level of micronutrients in oral mucosa diseases were included. The quality of case-control studies was assessed using the quality assessment tool developed by the National Heart, Lung and Blood Institute and Research Triangle Institute International. Results: There were 23 case-controlled studies were included in this study. Three studies investigated micronutrients level in recurrent aphthous stomatitis, 5 studies in oral submucous fibrosis, 8 studies in oral lichen planus, 6 studies in oral potentially malignant disorders and oral cancer and 1 study in another oral mucosa diseases. Overall, only 1 (4,35%) was assessed as poor-quality rating. Based on this review, there was a positive association between malnutrition (excess and low) of micronutrients and oral mucosa diseases. Conclusion: There is a relationship between malnutrition, either excess or lack of micronutrients on oral mucosal diseases.